Příspěvek ke studiu náboženských poměrů na ledečském panství na přelomu 16. a 17. století - Mirošovská, Eva (Lidé města, 2008)
The article shortly describes the character of the religious conditions at the Ledeč estate, situated in East Bohemia. It especially deals with the era at the turn of the 16th and 17th centuries. This era in Ledeč, associated with the Lobkovic administration and reign, was namely one of the last epochs of religious tolerance for Non-Catholics. The „Post-White Mountain” era then brings on the forced re-Catholicization, chiefly affecting those inhabitants who were subjects. For Non-Catholics, it meant either the involuntary acceptance of the Catholic religion or unwanted emigration. The article closely deals with archival sources and analyzes the edited Religious Order of the Ledeč Estate dating from 1599. The estate at that time was headed by Ladislav Lobkovic (senior). The order was addressed to subjects. The autohor endeavored to point out its non-Catholic character, even though presented by the editor, J. K. Hraše, as a Catholic order. The article also touches upon the epoch of the reign of Trčka family in the Ledeč estate, highlighting the outstanding persona of Jan Rudolf Trčka of Lípa.